Strategi Promosi Digital dalam Menarik Minat Beli Konsumen PT Sinverho Energi Indonesia - Wala Erpurini; Irfan Kurnia Ramadhan; Suci Indahsari (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2023)
he research is intended to determine the digital promotion strategy in attracting the purchasing interest of customers of PT Sinverho Energi Indonesia. The objectives of this study are to determine the utilization of social media as part of digital promotion, identify factors that support and hinder digital promotion, determine the digital promotion strategy in attracting customer purchasing interest, and identify the differences in promotion using Facebook Ads, Instagram Ads, and TikTok Ads. This research uses a qualitative-descriptive method, where the study reveals the social situation to be thoroughly, broadly, and deeply examined. The results of observations made during the study produced data as information to analyze the digital promotion strategy in attracting customer purchasing interest of PT Sinverho Energi Indonesia. In this study, snowball sampling method was used to interview several key informants. The data obtained were all documents related to company promotions. The conclusion of this research is that PT Sinverho has sufficiently conducted promotions, but has not maximized the utilization of social media and official website. The factors hindering this are the lack of dedicated human resources for digital marketing. The digital promotion strategy in attracting customer purchasing interest of PT Sinverho Energi Indonesia is analyzed using EFAS, IFAS, and SWOT analysis. The differences in promotion using Facebook Ads, Instagram Ads, and TikTok Ads are analyzed based on their features and ways of working.